Ensuring sustainability of conventional aerobic wastewater treatment system via bio-augmentation of aerobic bacterial consortium: An enhanced biological phosphorus removal approach. (20th July 2020) - Yadav, Dharmender; Singh, Nitin Kumar; Pruthi, Vikas; Kumar, Pramod
Abstract: Enhanced biological phosphorus removal (EBPR) is an inevitable need of sustainable waste water treatment systems (WWTS). In this regard, this study aimed to investigate the potential of an aerobic continuously stirred tank reactor (CSTR), enriched with selected bacterial consortium, for enhanced phosphorus removal. The CSTR biomass was bioaugmented through addition of 12 distinct phosphorus accumulating and solubilizing strains. The medium and high strength synthetic waste water, having the phosphorus concentration in the range of 1.4–40 mg/L, was fed to the CSTR throughout this study. With respect to medium strength feed, total phosphorus (TP) removal efficiency reached up to 90% at an influent concentration of 20 mg/L, followed by a declining trend of removal efficiency as 62 and 30%, at the TP concentration of 30 and 40 mg/L, respectively. Contrary, the EBPR activity was observed to be inhibiting (lesser accumulation of phosphorus in biomass) at lower influent TP value of 10 mg/L, when the CSTR was operated with high strength waste water. Further, ammonical nitrogen and chemical oxygen demand removal performance of the system was observed to be independent of influent TP concentration. Detailed experimental investigations revealed that the inoculated bacterial consortium favored the transformation and storage of influent TP into intracellular storage of polyphosphate (poly-P). Overall, the results indicated that the sustainability of existing WWTS can be ensured through bioaugmentation of non-EBPR sludge to aerobically cultivated EBPR performing sludge. Graphical abstract: Image 1